1998
DOI: 10.1021/es9804058
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Dissolution of Cinnabar (Mercuric Sulfide) by Dissolved Organic Matter Isolated from the Florida Everglades

Abstract: Organic matter isolated from the Florida Everglades caused a dramatic increase in mercury release (up to 35 μM total dissolved mercury) from cinnabar (HgS), a solid with limited solubility. Hydrophobic (a mixture of both humic and fulvic) acids dissolved more mercury than hydrophilic acids and other nonacid fractions of dissolved organic matter (DOM). Cinnabar dissolution by isolated organic matter and natural water samples was inhibited by cations such as Ca2+. Dissolution was independent of oxygen content in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
186
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(201 citation statements)
references
References 28 publications
12
186
3
Order By: Relevance
“…UV-vis spectroscopy analysis of all samples and controls without clays in batch adsorption experiments was conducted with a UV759S spectrometer (Shanghai Precision & Scientific Instrument, China) equipped with a quartz cell of 1.0 cm path length. Specific UV absorbance (SUVA) at 254 nm (SUVA 254 nm = UV 254 nm /TOC) was used as an index of relatively aromaticity of dissolved organic carbon (DOC) [21,22].…”
Section: Characterizationsmentioning
confidence: 99%
“…UV-vis spectroscopy analysis of all samples and controls without clays in batch adsorption experiments was conducted with a UV759S spectrometer (Shanghai Precision & Scientific Instrument, China) equipped with a quartz cell of 1.0 cm path length. Specific UV absorbance (SUVA) at 254 nm (SUVA 254 nm = UV 254 nm /TOC) was used as an index of relatively aromaticity of dissolved organic carbon (DOC) [21,22].…”
Section: Characterizationsmentioning
confidence: 99%
“…However, previous studies showed that dissolution of mercury sulfide (e.g., cinnabar) can also serve as a continuous source of inorganic Hg in natural environment due to the fact that a variety of environmental factors can facilitate its dissolution. These factors include the presence of iron(III) in acidic water [4], sulfide in water [5], and dissolved organic matter (DOM) [6][7][8]. The enhanced dissolution of cinnabar could be an important process controlling Hg cycling in aquatic environments as this process would make the originally stable Hg more reactive and bioavailable, increasing the possibility of Hg transport, methylation and bioaccumulation, posing a great risk to humans and wildlife.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of environmental factors are expected to enhance or inhibit cinnabar dissolution via affecting the fate of cinnabar dissolution products. These factors include pH, redox potential (Eh), and Hg binding ligands [4,7,12,13]. Sulfide (S 2− ), one of the cinnabar dissolution products, could be eliminated from the system via oxidation to SO 4 2− at pH 5-8 under aerobic condition [4,10,12,14,15] or conversion to HS − and H 2 S under anaerobic condition [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In anoxic, sulfidic sediments, cinnabar can dissolve and become available for methylation (Benoit et al 2001). Organic acids from vegetation can enhance the dissolution of cinnabar (Ravichandran et al 1998) and increase the transport of colloidal Hg from former mining sites (Slowey et al 2005).…”
Section: Introductionmentioning
confidence: 99%